Pengembangan Sistem Aplikasi Parentstory Aktivitas Anak Pada PT. Cerita Buah Hati Berbasis Android - Muhammad Aditya Pramudita; Bayu Priyambadha; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Children are the gift of God Almighty who must be grateful and become something beautiful for someone who is married. But not even the least parents who pay less attention to the child's growth needs, especially the need for educational activities that help him find hobbies, characteristics, and aspects that help child growth and development. Various problems were faced when the community or especially parents who want to find the best place for their children with all the work or other business activities. One of the ways that the author offers is through the media of Android applications as a medium of information and ordering educational children's activities. In the development of applications, the Waterfall method was used which began with interviews with parents who had children aged 9 months - 4 years. Then the application is designed with the Object Oriented Design method and implemented with the Object Oriented Programming method. The result of the implementation is that the application utilizes the programming language kotlin programming and the use of webservice for the process of exchanging data through the API (application programming interface) that has been made at the implementation stage. The system has been tested by unit testing for the 3 main functions of the system, validation testing for all needs, testing produces valid values ​​for all test cases. While at the usability testing stage with the System Usability Scale (SUS) method this application gets a score of 83 with satisfaction levels Very Good (SB) or above average.